Changes in left and right ventricular two-dimensional echocardiographic speckle-tracking indices in pediatric LVAD population: A retrospective clinical study. Issue 12 (December 2019) - Iacobelli, Roberta; Di Molfetta, Arianna; Cobianchi Bellisari, Flavia; Toscano, Alessandra; Filippelli, Sergio; Di Chiara, Luca; Pasquini, Luciano; Iorio, Fiore Salvatore; Amodeo, Antonio
Echocardiographic strain and strain-rate imaging is a promising tool for the evaluation of myocardial segmental function, for the early detection of myocardial dysfunction, and for the prediction of reverse remodeling. We aimed at studying the changes in left and right ventricular function in pulsatile left ventricular assist device pediatric patients by two-dimensional echocardiography and two-dimensional speckle-tracking echocardiography. Echocardiographic and clinical data of patients implanted with a pulsatile-flow left ventricular assist device from 2011 to 2018 were retrospectively reviewed before and after implantation at 1, 3, and 6 months. A total of 18 patients were enrolled. Median age and weight at implantation were 9 months (5–23 months) and 5.85 kg (4.85–8.75 kg), respectively; median left ventricular assist device support was 181 (114.5–289.5) days. 13 patients (73%) were transplanted and 5 patients (27%) died. At follow-up: left ventricular ejection fraction increase at 1 month (p = 0.001) and 3 months (p = 0.01), left ventricular global longitudinal strain improvement at 1 month (p = 0.0008) and 3 months (p = 0.02), and right ventricular free-wall longitudinal strain increase at 1 month (p = 0.01). At short term after left ventricular assist device implantation, both left ventricular and right ventricular mechanics improved. The temporary benefit seems to decrease over time. The worsening of left ventricular function has been followed by a worsening of right ventricular function probably due to the ventricular interdependence.